Informant Discrepancies in the Assessment of Attention-Deficit/Hyperactivity Disorder. (March 2018) - Kennerley, Stephanie; Jaquiery, Ben; Hatch, Burt; Healey, Matthew; Wheeler, Benjamin J.; Healey, Dione
An attention-deficit/hyperactivity disorder (ADHD) diagnosis requires symptoms to be present across two or more settings, thus requiring information from multiple informants. Research consistently shows low to moderate agreement between parents and teachers; however, the mechanisms underlying these discrepancies remain unclear. This study examined (a) agreement between parents and teachers, (b) effects of using different combination rules in assigning diagnoses, and (c) the role of contextual influences and/or personal biases in informants' reports. Fifty-five children, their parents, and teachers participated. Parent and teacher ratings on the Attention-Deficit/Hyperactivity Disorder Rating Scale–Fourth edition (ADHD-RS-IV) and clinician ratings on the Behavioral Observation of Students in Schools (BOSS) were obtained. Results indicated moderate agreement among parent and teacher ratings on the ADHD-RS. Diagnostically, the rule for combining information from multiple informants dramatically altered the ADHD classification assigned to the child. With regard to rater differences, the clinician-rated school observation gave some support for the notion that ratings are person rather than context specific.